(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Lumbar hernias are rare in children. We report a case of bilateral lumbar hernia in a 39 days old boy who was admitted at pediatric surgery department in Dhaka Medical College Hospital with the chief complaints of bilateral flank swellings since birth. There were no urinary or bowel complaints. Palpation revealed reducible, non-tender, soft to firm swellings involving iliolumbar region in left and lumbar region in right . These were increased on crying. On auscultation bowel sounds were present in left side and absent in right side. There were no other congenital anomalies.Ultrasonography revealed herniated bowel loops in left iliolumbar region and mild pelvicalicial dilatation in left kidney and slightly bigger right kidney in right lumbar region. On the basis of these findings a diagnosis of congenital bilateral lumbar hernias were made. Closer of the defects were done by prosthetic material and non- absorbable suture material. He came back for follow-up after 2 weeks, 4 weeks and 6 weeks. Defects were clinically absent and the patient was pain and recurrence-free. DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19537